Investigation of low voltage Fabry-Perot modulators for optical interconnect applications - Byrne, Declan James (Trinity College (Dublin, Ireland). School of Physics, 2001)
Optical interconnect technology is one of the proposed solutions to the fast approaching communication bottleneck in electronic digital systems, arising from the bandwidth limitations of electrical interconnects. Optical modulators are a key technology in optical interconnect systems that can potentially provide the terabit (10 12) per second data rates required by future electronic systems. The optical technology used in such optical systems must fulfil many requirements for operation in what is a complex environment. One possible solution is an epitaxially grown semiconductor modulator structure, consisting of multiple quantum wells with an optical mirror or mirrors to form a modulator. Current devices with one back mirror operate sufficiently at current electronic supply voltages (=5V) but operation at lower voltage required by falling electronic supply voltages (=1V) does not produce the modulation depth required by digital systems to differentiate between digital logic values. The addition of a second mirror to this structure to form a Fabry-Perot modulator changes the physics of the device operation and has been shown to allow lower voltage operation to be possible. The use of an resonant structure strongly influences the device characteristics such as its spectral bandwidth, angular range of operation, sensitivity to changing ambient temperature, optical saturation, and most importantly its sensitivity to variations in optical cavity thickness that determines the possible device arrays size. In this thesis the potential for low voltage operation of these modulator devices is explored particularly with reference to the InGaAs system and the resulting impact on the device operating tolerances is calculated. This work is part of a project to construct a working optical interconnect system and the operating tolerances are compared to the requirements of a real system. The approach taken is to develop a numerical model combined with experimental measurements to simulate the optical characteristics of the devices allowing the potential limits of operation of such devices to be explored. Fabry-Perot modulators using a metal mirror and Bragg mirror are first examined revealing the main parameters that govern the modulation achievable in a cavity structure and the device structure required at lower voltage operation. This work also revealed the limitations on the modulation achievable using a metal coating as an optical mirror, especially when it must also function as an electrical contact. Fabry-Perot modulators using two Bragg mirrors to form the optical cavity are shown to be necessary at very low voltages and show the back mirror reflectivity is critical to these devices. Although very low voltage operation is shown to be possible, an investigation of the device tolerances reveals poor results due to the high cavity finesse and long optical cavity length. The poor tolerances are shown to be improved by the use of a short optical cavity, a so called ‘microcavity modulator’ device reveals the device tolerances and sensitivity to cavity thickness variation can be dramatically improved at very short cavity lengths of the order of a few wavelengths in size. The tolerances of these devices are examined with respect to the potential of existing technologies. Finally the lowest possible operating voltage using InGaAs modulator devices is concluded and an ideal device structure for low voltage operation is summarised.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin